(untitled) (Palíndromo, 2021)
There are countless texts that the Brazilian artist Hélio Oiticica wrote during his life. From concepts to theoretical essays, from letters to projects, from inscriptions to poems, Oiticica used the word to organize and present his work to the world. This article aims to discuss the public poetry of Oiticica when he was in Rio de Janeiro, between 1965 and 1968, whose composition is made up of 19 texts inscribed in Parangolés, Bólides and a flag. Subsequently, two inscriptions will be analyzed, the Parangolé P11 Capa 7 (1966), with “Estamos Famintos”, and the Parangolé P18 Capa 16 (1968), with “Sexo e violência: eis o que me agrada”. It is intended, therefore, from the visual and textual aspects of the works, to highlight the notion of “strange fruits”, by Florencia Garramuño, which designates artistic objects of difficult classification, hybrids.